Impact of Vaccines; Health, Economic and Social Perspectives - Rodrigues, Charlene M. C.; Plotkin, Stanley A. (Frontiers in Microbiology, 2020)
In the 20th century, the development, licensing and implementation of vaccines as part of large, systematic immunisation programmes started to address the health inequities the existed in the world. However, at the time of writing, access to vaccines that prevent life-threatening infectious diseases remains unequal to all infant, children and adults in the world. This is a problem that many individuals and agencies are working hard to address globally., As clinicians and biomedical scientists we often focus on the health benefits that vaccines provide, in the prevention of ill-health and death from certain infectious pathogens. Here we discuss the health, economic and social benefits of vaccines that have been identified and studied in recent years, impacting all regions and all age groups. After learning of the emergence of SARS-CoV-2 virus in December 2019, and its potential for global dissemination to cause COVID-19 disease was realised, there was an urgent need to develop vaccines at an unprecedented rate and scale. As we appreciate and quantify the health, economic and social benefits of vaccines and immunisation programmes to individuals and society, we should endeavour to communicate this to the public and policy makers, for the benefit of endemic, epidemic and pandemic diseases. .